2022
DOI: 10.3390/cells11050881
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Cell-Cycle Progression by Hydrogen Peroxide-Mediated Cross-Linking and Degradation of Cell-Adhesive Hydrogels

Abstract: The cell cycle is known to be regulated by features such as the mechanical properties of the surrounding environment and interaction of cells with the adhering substrates. Here, we investigated the possibility of regulating cell-cycle progression of the cells on gelatin/hyaluronic acid composite hydrogels obtained through hydrogen peroxide (H2O2)-mediated cross-linking and degradation of the polymers by varying the exposure time to H2O2 contained in the air. The stiffness of the hydrogel varied with the exposu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 79 publications
6
19
0
Order By: Relevance
“…The dynamic trend in the mechanical property of the hydrogel that shows an initial increase, which peaked at 30 min, followed by a reduction in the Young’s modulus in prolonged exposure time ( Figure 2 d) is consistent with our previous studies on Gelatin-Ph hydrogel and Gelatin-Ph/HA-Ph composite hydrogel [ 15 , 17 ]. The decreased Young’s moduli of Gelatin-Ph hydrogel in prolonged exposure to air containing 16 ppm H 2 O 2 could be a consequence of cross-linking inhibition due to HRP inactivation.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…The dynamic trend in the mechanical property of the hydrogel that shows an initial increase, which peaked at 30 min, followed by a reduction in the Young’s modulus in prolonged exposure time ( Figure 2 d) is consistent with our previous studies on Gelatin-Ph hydrogel and Gelatin-Ph/HA-Ph composite hydrogel [ 15 , 17 ]. The decreased Young’s moduli of Gelatin-Ph hydrogel in prolonged exposure to air containing 16 ppm H 2 O 2 could be a consequence of cross-linking inhibition due to HRP inactivation.…”
Section: Resultssupporting
confidence: 91%
“…At 5.0% w / v , the Gelatin-Ph solution quickly forms hydrogel at room temperature, while at 1.0% w / v , the resultant hydrogels are too weak to handle for experiments. In addition, 1 U mL −1 HRP is used, since previous studies have reported an H 2 O 2 -mediated dynamic of the stiffening and softening of the hydrogels using a similar setup [ 15 , 17 ]. The scanning electron microscope (SEM) observation on the cross-section of the hydrogels showed a porous structure with a pore diameter of 28–42 µm ( Figure S2 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Induction of cytotoxicity, including DNA damage and apoptosis, by oxidative stimuli is mostly accompanied by cell cycle arrest. Many previous studies have indicated that the cytotoxic effect of H 2 O 2 is closely related to cell cycle arrest at the G2/M phase (Ding et al, 2019;Mubarok et al, 2022). Similar results were also observed in this study using C2C12 myoblasts due to an increase of Cdk inhibitor p21, a negative regulator of cell cycle progression, and decreases of cyclin A and cyclin B1 required for G2 to M phase progression (Dai et al, 2019;Taylor & Stark, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Benefits of H 2 O 2 sterilization are similar to those of other chemical sterilants, including relatively low operating temperatures and better compatibility with heat sensitive polymers. , Compared to EtO gas, however, vaporized H 2 O 2 has less effective penetration of porous scaffolds ,,,, Furthermore, although deliberate H 2 O 2 incorporation the in polymeric scaffold may be leveraged for certain drug delivery or tissue engineering applications, the hydroxyl free radical generated during H 2 O 2 sterilization has the potential to oxidatively cross-link polymers, resulting in deleterious changes. ,, Studies characterizing the morphological and biochemical changes induced by H 2 O 2 sterilization in UHMWPE revealed changes similar to those induced by gamma irradiation, including embrittlement . H 2 O 2 sterilization has also been observed to induce mechanical and degradative property changes to degradable polymers such as PLA. ,, Lastly, it is of note that H 2 O 2 sterilization was found to be ineffective when paired with cellulose-based products due to the high tendency of cellulose to absorb H 2 O 2 , thereby reducing its effective concentration .…”
Section: Fda Established Sterilization Methodsmentioning
confidence: 99%